Thermo-economic analysis of reverse water-gas shift process with different temperatures for green methanol production as a hydrogen carrier. Issue 41 (October 2020) - Elsernagawy, Omar Y.H.; Hoadley, Andrew; Patel, Jim; Bhatelia, Tejas; Lim, Seng; Haque, Nawshad; Li, Chao'en
Highlights: Thermo-economic analysis of RWGS with different temperatures were performed; Reaction parameters were optimized; Higher temperature RWGS has advantage in heat integration; Plant scale, H2 production, and labor cost affect OPEX the most. Abstract: The development of renewable energy makes it possible to produce abundant hydrogen as the energy carrier. For reducing the hydrogen storage and transportation cost, methanol synthesis via reverse water gas shift (RWGS) reaction can provide significant environmental benefits through a carbon capture and utilization pathway. There have been researches in the past to determine the most effective catalysts and related technologies in process development. However, a remaining question has been whether it should be run at a temperature above 900 °C where problematic by-products and coke might be an issue, or below 500 °C where it is not kinetically favored, but heavy catalyst use could compensate. This paper investigated the tradeoff between running the RWGS process at the higher or the lower temperature range as part of a methanol (MeOH) production plant. The plant had a basis of 80 kmol/hour of methanol product. A process flowsheet for each route was developed and optimized using ASPEN Plus as well as heat integration methods. The carbon footprint was then calculated to assess the environmental performances of both processes. Finally, an economic analysis was conducted to assess the overall feasibility for implementing either process. It was found that while running the process at a lower temperature of 450 °C requires a lower energy consumption, however it comes with a higher cost due to the heavy reliance on the catalytic reaction. The higher temperature reaction running at 940 °C performed similarly to the lower temperature reaction but with a better environmental performance and lower cost of production. Moreover, using a higher production capacity for the plant proved a higher promise of eliminating economic issues due to economies of scale.